Formulation and Evaluation of Rifampicin Microspheres for Lung Targeting - Sharma, Anurag; Agrawal, Dilip; khinchi, M.P.; Sharma, Natasha; Gupta, M. K. (Asian Journal of Pharmaceutical Research and Development, 2013)
The present investigation was aimed to develop lung targeting microspheres as drug carriers to reduce dose/dosing frequency in the management of tuberculosis. Microspheres of rifampicin were prepared by using Eudragit L100 and Eudragit RLPO by solvent evaporation technique and microspheres of rifampicin were prepared with natural polymer chitosan by emulsion polymerization technique. Rifampicin microspheres were prepared by using each polymer in drug to polymer ratio of 1:1, 1:2, 1:3 and 1:4 respectively. The microspheres were evaluated for surface morphology, SEM, percentage yield, average particle size, % drug entrapment efficiency and in vitro drug release studies. The particle sizes of the microspheres were found to be in the range of 18±3µm and 47±3µm. Rifampicin microspheres were found to be slightly rough surfaced but spherical and good appearance. The drug entrapment efficacy of Rifampicin microspheres was found to be in the range of 74.8% –95.5%. In vitro drug release after 8 hour was found to be in the range of 71.52%-97.1%. Rifampicin microspheres could be suitable and utilized for targeting rifampicin to the lung.